2006
DOI: 10.1111/j.1365-2788.2006.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of stimulation versus microswitch‐based programmes on indices of happiness of students with multiple disabilities

Abstract: Microswitch-based programmes might be deemed preferable to stimulation programmes because they can promote higher or comparable indices of happiness while promoting the acquisition of adaptive responses and self-determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The literature on the use of microswitches and contingent stimuli for promoting ambulation responses among pediatric populations is substantial (Lancioni et al, , 2013; Lancioni, Singh, O'Reilly, Sigafoos, Alberti,et al ). Previous studies have shown the effectiveness of microswitch use among individuals with multiple disabilities (Lancioni & Singh, ; Perilli, Lancioni, Laporta, et al, ).…”
mentioning
confidence: 99%
“…The literature on the use of microswitches and contingent stimuli for promoting ambulation responses among pediatric populations is substantial (Lancioni et al, , 2013; Lancioni, Singh, O'Reilly, Sigafoos, Alberti,et al ). Previous studies have shown the effectiveness of microswitch use among individuals with multiple disabilities (Lancioni & Singh, ; Perilli, Lancioni, Laporta, et al, ).…”
mentioning
confidence: 99%
“…Most of the studies were published in the last decade ( n = 24); the remaining studies were published between 1997 and 2010. In 29 studies, a single case design was used (Dunphy & Hens, 2018 ; Gaskin et al, 2012 ; Hetzroni & Banin, 2017 ; Hronis et al, 2019 ; Kim et al, 2014 ; ; Lancioni, O’Reilly, et al, , 2006 , 2013 ; Lancioni, Singh, O’Reilly, Green, et al, 2014 ; Lancioni, Singh, et al, 2006 , 2013 ; Lancioni, Singh, O’Reilly, Sigafoos, et al, 2014 ; Lancioni, Smaldone, et al, 2006 ; Perilli et al, 2019 ; Simacek et al, 2017 ; Singh et al, 2017 ; Stasolla, Damiani, et al, 2014 ; Stasolla & O’Caffò, 2013 ; Stasolla et al, 2013 , 2015 , 2017a ; Stasolla, Perilli, Caffò, et al, 2017 ; Stasolla, Perilli, et al, 2014 ). In addition, two studies used a pre‐experimental design (Hoffman et al, 2017 ; Jonker et al, 2015 ) and one study used a randomized control trial (Cooney et al, 2017 ), while one study did not report about the study design (Monlux et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of the studies ( n = 29) reported on interventions that were delivered at the individual level (Cooney et al, 2017 ; Dunphy & Hens, 2018 ; Gaskin et al, 2012 ; Hoffman et al, 2017 ; Jonker et al, 2015 ; Kim et al, 2014 ; ; Lancioni, O’Reilly, et al, 2013 , 2006 ; Lancioni, Singh, O’Reilly, Green, et al, 2014 ; Lancioni, Singh, et al, 2006 , 2013 ; Lancioni, Singh, O’Reilly, Sigafoos, et al, 2014 ; Lancioni, Smaldone, et al, 2006 ; Perilli et al, 2019 ; Singh et al, 2017 ; Stasolla, Damiani, et al, 2014 ; Stasolla, Perilli, Caffò, et al, 2017 ; Stasolla, Perilli, Damiani, et al, 2017 ; Stasolla, Perilli, et al, 2014 ; Stasolla et al, 2015 ). In addition, two interventions were delivered to a dyad comprising a child with an intellectual disability and his/her parent (Monlux et al, 2019 ; Simacek et al, 2017 ), while two studies reported on a combination of a group intervention with individual elements, such as a group discussion combined with playing video games individually (Hetzroni & Banin, 2017 ; Hronis et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations